Accuracy of a Novel Scoring System for Prediction of Response to Neoadjuvant Chemotherapy in Locally Advanced Breast Cancer Patients - Nurindah Dwi Utami; Nur Qodir; Erial Bahar (Sriwijaya Journal of Surgery, 2021)
Background: Neoadjuvant chemotherapy (NAC) has become a widely accepted treatment option for locally advanced breast cancer (LABC). Furthermore, response to NAC is considered to be a predictor of favorable outcomes. It is known that some predictors are associated with NAC response. Objectives: To assess the accuracy of scoring system for prediction of response to neoadjuvant chemotherapy in LABC. Methods: Medical record of 50 patients received NAC at Mohammad Hoesin Hospital were retrospectively analysed between July 2019 to July 2020. Response of NAC in LABC was determined with Response Evaluation Criteria in Solid Tumours (RECIST). Variables of the scoring system are risk factors of breast cancer, immunohistochemical subtype, CD4+, CD8+, CD4+/CD8+ ratio, and neutrophil to lymphocyte ratio. Results: A total of 50 patients with LABC received and completed NAC. The mean age was 48.2 Â± 11.0 at the time of diagnosis. Good response to NAC was achieved in 38 patients (76.0%). This scoring system shows a sensitivity of 77.8%, a specificity of 83.3%, a positive predictive value of 18.4%, and a negative predictive value of 24.4% with the Youden index of 66.1. The combination between less than three parity and positive estrogen receptor demonstrated better accuracy with a sensitivity of 96.3% and specificity of 77.7% and Youden index 74. Conclusion: This pilot study suggests that this scoring system is potentially useful for predicting response to neoadjuvant chemotherapy in LABC patients and warrants further investigation in a larger population to validate this finding.